AB0630 Cardiac Magnetic Resonance Imaging with Pharmacological Stress Perfusion in Asymptomatic Patients with Systemic Sclerosis. (15th July 2016) - Ruscitti, P.; Di Cesare, E.; Cipriani, P.; Di Sibio, A.; Liakouli, V.; Gennarelli, A.; Carubbi, F.; Splendiani, A.; Berardicurti, O.; Di Benedetto, P.; Ciccia, F.; Guggino, G.; et al.
Abstract : Background: Systemic Sclerosis (SSc)-heart disease (SSc-HD), although often clinically silent, significantly reduces the life-expectancy in these patients [1]. The cardiac magnetic resonance (CMR) is recognized useful tool for the diagnosis of SSc-HD and cardiac stress tests might be a helpful technique to highlight the occult myocardial involvement, which cannot be detected at rest due to compensatory mechanisms [2, 3]. Objectives: To evaluate the possible occult cardiac involvement in asymptomatic SSc patients by pharmacological stress, rest perfusion and delayed enhancement CMR, to identify as earlier as possible those patients at higher risk of cardiac related mortality and needing specific cardiovascular treatments. Methods: Sixteen consecutive patients with definite SSc fulfilling the ACR/EULAR 2013 classificative criteria [4] in less than 1 year from the onset of Raynaud's phenomenon underwent pharmacological stress, rest perfusion and delayed enhancement CMR. No enrolled patient showed signs and/or symptoms suggestive for cardiac involvement, confirmed by both the 12-lead ECG examination and echocardiography. No patient showed traditional cardiovascular risk factors. Patients, in which CMR technique showed occult cardiac involvement, underwent to heart computed tomography (CT) scan to evaluate a possible coronary disease. Results: Stress perfusion defects, in the left ventricle, were detected in 6 out of 16 (37.5%) patients. A sub-endocardial defects and/or a ventricular mid-myocardial layer stress perfusion defects were observed. Our results confirmed, in these 6 patients, a normal flow distribution of the explored coronary arteries by CT scan. The presence of CMR stress perfusion defects did not correlate with any clinical feature of patients. Conclusions: Myocardial stress perfusion defects may be early detected, by pharmacological stress perfusion CMR, a reliable and sensitive technique for the non-invasive evaluation of SSc-HD, in patients with SSc of recent onset. These defects seems to be independent from traditional risk factors and associated comorbidities, suggesting that are a specific hallmark of the disease. An early detection of myocardial involvement might suggest starting of vasodilatative therapies in these patients. References: Allanore Y, et al. Primary myocardial involvement in systemic sclerosis: evidence for a microvascular origin. Clin Exp Rheumatol 2010;28:S48–53. Di Cesare E, et al. Early assessment of sub-clinical cardiac involvement in systemic sclerosis (SSc) using delayed enhancement cardiac magnetic resonance (CE-MRI). Eur J Radiol. 2013;82:e268–73. Hachulla AL, et al. Cardiac magnetic resonance imaging in systemic sclerosis: a cross-sectional observational study of 52 patients. Ann Rheum Dis. 2009;68:1878–84. van den Hoogen F, et al. 2013 Classification Criteria for Systemic Sclerosis An American College of Rheumatology/European League Against Rheumatism Collaborative Initiative. Arthritis Rheum. 2013;65:2737–47. Disclosure of Interest: None declared